Influence of the Reaction Conditions in the Crystal Structures of Zn(II) and Ni(II) Coordination Compounds with a Dissymmetric Bis(Thiosemicarbazone) Ligand - Luis Alonso; Rodrigo Burón; Elena López-Torres; Maria Antonia Mendiola (Crystals, 2022)
The new ligand HMeATSM, derived from condensation of 2-3-butanedione with 4-methyl-3-thiosemicarbazide and 2,4-dimethyl-3-thiosemicarbazide, has been synthesized. Its reactivity with nickel(II) and zinc(II) nitrates was explored and the resulting complexes were thoroughly characterized by elemental analysis, conductivity, mass spectrometry, IR, 1H and 13C NMR spectroscopies and their structures were confirmed by single-crystal X-ray diffraction. The results showed that the complex [Ni(MeATSM)]NO3 1 is formed under every reaction condition. In contrast, the reaction with zinc(II) nitrate depends on the temperature and the presence of LiOH·H2O, leading to the obtaining of complexes [Zn(MeATSM)(OH2)](NO3) 2 and [Zn(Me2TS)2(OH2)](NO3)2 3. The crystal structures of complexes 1 and 2 show that the dissymmetric ligand acts as a N2S2 tetradentate monoanionic ligand. The structural preferences of the metals also determine the structure of the complexes: whereas nickel(II) is in a square-planar environment, the zinc atom prefers a distorted square-base pyramid geometry imposed by the coordination mode and the planarity of the bis(thiosemicarbazone) ligand. In contrast, in complex 3, containing two bidentate Me2TS ligands, the Zn(II) is in a trigonal bipyramid arrangement. In all the complexes, the nitrate ion is not coordinated to the metal and acts as a counterion.